Magnetic transition and large magnetocaloric effect associated with surface spin disorder in Co and CocoreAgshell nanoparticles - Poddar, P.; Srinath, S.; Gass, James; Bhagavatula L. V. Prasad; Srikanth, H. (Journal of Physical Chemistry C, 2007)
We report a reversible, large magnetocaloric effect in the vicinity of a low-temperature magnetic transition in Co and CocoreAgshell nanoparticles synthesized using a wet chemical method. The as-synthesized assembly of the particles shows a sharp low-temperature peak in the zero-field-cooled (ZFC) magnetization well below the blocking transition temperature, and this feature is associated with the surface spin disorder. Co nanoparticles show a large increase in the magnetic entropy at around 15 K with a peak value of nearly 2.25 J/K center dot kg for an applied field of 30 kOe. A similar trend is also observed in the silver-coated Co particles. These are some of the largest NICE values observed in nanoparticles to date. The features are ascribed to the low-temperature spin-glass-like freezing transition associated with the surface spins in the shell region that is distinct from the behavior of core spins. Our studies reveal that manipulating the surface anisotropy in core-shell nanoparticles has the potential to lead to a large NICE effect and thus prove to be useful for magnetic refrigeration.

Static and dynamic magnetic properties of Co nanoparticles - Srinath, S.; Poddar, P.; Sidhaye, Deepti S.; Bhagavatula L. V. Prasad; Gass, James; Srikanth, H. (Journal of Nanoscience and Nanotechnology, 2008)
Co nanoparticles have been synthesized using wet-chemical methods. As-synthesized particles show a sharp low temperature peak in zero-field cooled (ZFC) magnetization well below the blocking transition temperature and this feature is associated with surface spin disorder. We have investigated the dynamic magnetic properties of Co using ac susceptibility and resonant RF transverse susceptibility (TS). We also studied the memory and relaxation effects in these nanoparticle systems. From these measurements we show a typical blocking behavior of an assembly of superparamagnetic nanoparticles with a wide distribution of blocking temperatures. The transverse susceptibility measurements on these particles show the presence of anisotropy even above the blocking temperature. The role of surface anisotropy and the size distribution of the particles on the observed memory and magnetic relaxation effects are discussed.
Keywords: Ac Susceptibility; Co Nanoparticles; Magnetic relaxation; Transverse Susceptibility

Large magnetocaloric effect, moment, and coercivity enhancement after coating Ni nanoparticles with Ag - Srinath, Sanyadanam; Poddar, Pankaj; Das, Raja; Sidhaye, Deepti; Bhagavatula L. V. Prasad; Gass, James; Srikanth, Hariharan (ChemPhysChem, 2014)
We observe a large magnetocaloric effect in monodisperse Ni and NicoreAgshell nanoparticles in the superparamagnetic region. The organically passivated Ni nanospheres show a large magnetic entropy change of 0.9 J kg(-1)K for a 3 T magnetic field change. In comparison to the surfactant-coated Ni nanoparticles, the NicoreAgshell nanoparticles show an enhanced coercivity, magnetization, and magnetocaloric effect (1.3 kgK for a 3 T magnetic field change). The coercivity at 10 K increases from 360 Oe for Ni nanoparticles to nearly 610 Oe for NicoreAgshell particles. This large enhancement is attributed to the enhanced inter-particle interaction, which is mediated by the metallic shell, over the relatively weaker dipolar interaction in the surfactant-coated Ni nanoparticles, and to modification of the surface spin structure.
Keywords: anisotropy; core-shell; magnetic properties; Nanoparticles; superparamagnetic